The local problem of God’s hiddenness: a critique of van Inwagen’s criterion of philosophical success - Soerensen, Jennifer L. (International journal for philosophy of religion, 2013)
In regards to the problem of evil, van Inwagen thinks there are two arguments from evil which require different defenses. These are the global argument from evil—that there exists evil in general, and the local argument from evil—that there exists some particular atrocious evil X. However, van Inwagen fails to consider whether the problem of God’s hiddenness also has a “local” version: whether there is in fact a “local” argument from God’s hiddenness which would be undefeated by his general defense of God’s hiddenness. This paper will argue that van Inwagen’s present account contains no implicit response to the “local” argument from God’s hiddenness, and, worse, the “local” argument brings to the fore crucial inconsistencies in van Inwagen’s account. These inconsistencies concern van Inwagen’s criterion for philosophical success—his methodological use of an “ideal audience” in an ideal debate—and a crucial premise in his argument: namely, that people who do not believe in God are culpably deceiving themselves regarding the manifest presence of God. These considerations will be a platform for my arguing that the failures of van Inwagen’s account amount to his ignoring the extra-rational, concrete aspect of grasping “spiritual propositions”—propositions which, in order to be affirmed, require the full self-understanding which precipitates out of the mind, body, and will of a particular existing individual.